The complete mitochondrial genome and phylogenetic analysis of the dwarf surf clam Mulinia lateralis. Issue 1 (2nd January 2020) - Liu, Jing; Zeng, Qifan; Wang, Hao; Teng, Mingxuan; Guo, Ximing; Bao, Zhenmin; Wang, Shi
Abstract: Mulinia lateralis (Say, 1822) is a species of the bivalve family Mactridae and represents a promising model species for molluscan research. In this study, the complete mitochondrial genome (mitogenome) of M. lateralis was sequenced and assembled for the first time. The 21, 668 bp mitogenome contained 13 protein-coding genes, 2 rRNAs, 22 tRNA genes, and an AT-rich region. The overall AT content (69.56%) was higher than GC content (30.44%). Phylogenetic analysis supported that M. lateralis belongs to the family Mactridae. The mitochondrial genome of M. lateralis provides a valuable resource for further understanding the phylogeny of the family Mactridae and for functional studies of molluscan mitochondrial genes.